Fabrication and characterization of structurally stable pH-responsive polymeric vesicles by polymerization-induced self-assembly. Issue 46 (31st August 2021) - Zhang, Fen; Niu, Yanling; Li, Yantao; Yao, Qian; Chen, Xiaoqi; Zhou, Haijun; Zhou, Mengmeng; Xiao, Jijun
Abstract : Smart polymeric vesicles with both tertiary amine and epoxy functional groups were fabricated for the first time via a reversible addition–fragmentation chain transfer dispersion polymerization approach. Abstract : Smart polymeric vesicles with both tertiary amine and epoxy functional groups were fabricated for the first time via a reversible addition–fragmentation chain transfer dispersion polymerization approach, using (2-(diisopropylamino)ethyl methacrylate (DIPEMA) and glycidyl methacrylate (GlyMA) in an ethanol–water mixture. Monitoring of the in situ polymerization revealed the low molecular weight distributions and the intermediate structures of spheres and worms, indicating an evolution in particle morphology. A phase diagram was constructed for reproducible fabrication of the vesicles, and copolymer composition was found to be more related to particle morphology. The vesicles exhibited superior structural stability for the cross-linking of the core through epoxydiamine chemistry, and intelligent pH responsibility due to the presence of the tertiary amine groups. The cross-linked vesicles showed good stability and reversibility during the swelling and shrinking cycles by switching the pH values, which endowed them with potential cell-like transmission functions. This research thus provides a method for producing structurally stable pH-responsive polymeric vesicles, and the reported vesicles are based on commercially available starting materials for possible industrial scale-up.